Preparation for total war: 'Military Service Preparation Camps' in the Turkish education system in the early Republican Era (1926-1946) - Gursoy, Ozlem; Gunduz, Mustafa (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2024)
Since the early nineteenth century, various ideologies have attempted to design education systems with an abundance of military attitudes for the future of the state and society, thereby benefiting paramilitary organizations and incorporating military educational practices into public education environments. In the aftermath of the two world wars, numerous countries, particularly nation-states, embraced the concept of militarised education systems. The incorporation of military methods into education dates back to the late Ottoman Period (after 1913). Following the establishment of the Republic in 1923, military courses were incorporated into the education curricula with the purpose of preparing the youth to confront the potential threats of war, fulfil security needs, and safeguard the homeland. After 1927, in addition to the theoretical courses, Military Service Preparation Camps were implemented. A decade later, this military camp approach was extended to all levels of education. As a result, the education system was transformed into learning environments where basic military skills and knowledge were taught. In this article, Military Service Preparation Camps, which were effectively implemented in the Turkish education system between 1926 and 1946, were investigated based on the primary sources and the recollections of individuals who actively participated in these camps. The primary objective of the military training camps, supervised and coordinated by the General Staff, was to 'prepare youth for homeland defence and total war, and to promote military service'. In this vein, this study seeks to unveil the impacts of rigorous military training on Turkish society, particularly in the post-1945 era.
Keywords: Militarism; Military Courses; Military Service Preparation Camps; Preparing for War; Total War; Education and Society; Area Studies